Extraperitoneally Ruptured, Everted, and Prolapsed Bladder: A Very Rare Complication of Pelvic Injury - Rufus Wale Ojewola; Kehinde Habeeb Tijani; Olakunle Olaleke Badmus; Abisola Ekundayo Oliyide; Chukwudi Emmanuel Osegbe (Case Reports in Urology)
Traumatic rupture of the bladder with eversion and protrusion via the perineum is a rare complication of pelvic injury. We present a 36-year-old lady who sustained severe pelvic injury with a bleeding right-sided deep perineal laceration. She had closed reduction of pelvic fracture with pelvic banding and primary closure of perineal laceration at a private hospital. She subsequently had dehiscence of repaired perineal laceration with protrusion of fleshy mass from vulva and leakage of urine per perineum five weeks later. Examination revealed a fleshy mucosa-like mass protruding anteriorly with a bridge of tissue between it and right anterolateral vaginal wall. Upward pressure on this mass revealed the bladder neck and ureteric orifices. She had perineal and pelvic exploration with findings of prolapsed, completely everted bladder wall through a transverse anterior bladder wall rent via the perineum, and an unstable B1 pelvic disruption. She had repair of the ruptured, everted, and prolapsed bladder, double-plate and screw fixation of disrupted pelvis and repair of the pelvic/perineal defect. She commenced physiotherapy and ambulation a week after surgery. Patient now walks normally and is continent of urine. We conclude that the intrinsic urethral continent mechanism plays a significant role in maintaining continence in females.